The struggle over pedestrians: Defining the problems of walking in the 1960s and 1970s - Männistö-Funk Tiina (SAGE PUBLICATIONS INC, 2025)
This paper considers the negotiations around walking in Finland in the 1960s and 1970s as a symbolic struggle. Quickly changing urban environment and high traffic fatality numbers brought pedestrians into the focus of public discussions during this era. Two major groups making claims over pedestrians were the traffic safety organisation Talja and its successor Liikenneturva as well as the traffic policy association Enemmisto. Traffic safety actors highlighted pedestrians' responsibility as a traffic mode among others, but also framed them as reckless and weak. Traffic policy activists used pedestrians as a lens to the unfairness of the car-centred traffic system and urban environment. Both tried to steer away from the simple antagonism between cars and pedestrians, but with little success. Whereas pedestrians were difficult to govern, due to their non-vehicle flexibility, they were also difficult to advocate for. The struggle ended in a compromise that rendered pedestrians invisible.